What do non-ophthalmic health professionals know about retinoblastoma: a survey in Saudi Arabia - AlHarkan, Dora H.; Almuzneef, Malak A.; Alhammad, Norah M; Alyousif, Nora A.; Alyousif, Lina A.; Alotaibi, Waad A.; Almayouf, Furat A. (International Journal of Research in Medical Sciences, 2019)
Background: The aim of the study is to estimate the level of knowledge about retinoblastoma (Rb) and its determinants among non-ophthalmic health professionals of Qassim region of Saudi Arabia. Methods: This cross-sectional survey was held in 2016 in primary health centres (PHC) and general hospitals in the study area. In addition to demography like age, gender, education, place of work, participants replied to five questions related to Rb with close-ended questions to respond. They were matched to the expert group's answers to estimate the level of knowledge. Results: One hundred and fifty-two non-ophthalmic doctors participated in the survey. The excellent grade of knowledge of Rb was in 66 [43.3% (95% confidence interval 35.5-51.3)] of participants. Very poor level of knowledge was noted in 13 [8.6% (95% CI 4.1-13.0)] participants. Male gender (P = 0.02) and physician category (P = 0.02) were significantly associated with the excellent grade of Rb related knowledge. The participant’s response by type of questions varied significantly (P<0.001). Conclusions: More than half of the non-ophthalmic health professionals had less than desired knowledge about Rb. Health education about Rb to health professionals could be gender sensitive and based on the type of profession. Increasing the awareness about retinoblastoma among non-ophthalmic health professional is important.